Designing and developing a programme-focused assessment strategy: a case study. (3rd May 2016) - Brunton, James; Brown, Mark; Costello, Eamon; Walsh, Elaine
Abstract: This case study describes the process that the Humanities Programme Team, in Dublin City University's Open Education Unit, has undertaken with regard to developing a systematic, programme-focused assessment strategy. It charts the development of an Assessment Matrix that facilitated the enhancement of programme coherence in the context of a distributed modular provision model, and facilitated the use of an appropriate range and scaffolding of assessment types in relation to learning outcomes. To conclude, four recommendations on developing a programme-focused assessment strategy are presented: explicitly link assessments to both programme and module learning outcomes; provide adequate supports and resources for those designing and writing assessments; provide those Assessment Writers with appropriate professional development, as well as an opportunity to be part of an assessment writing community; and to embed a programme-focused assessment strategy into a programme's quality assurance processes.